Dialectical Islamic and Confucian traditions within ASEAN to hinder the clash of civilization - Saefur Rochmat (Universitas Negeri Yogyakarta, 2016)
In the globalization era the clash of civilizations becomes our concern due to culture being the only aspect of human living not affected by globalization. But all aspects of human living are substantially related to culture for their meaning as well as the identity of certain groups differing from others. The clash of civilization discourses was ignited by Samuel P. Huntington who perceives the unification of Islamic Civilization and Confucian Civilization as the greatest threat to America. Inevitably the US has tried to attract the Confucian Civilization as its ally, leaving its former allies, the ASEAN countries, with their strong Islamic influence. However the ASEAN members have strong internal cohesion so they are able to manage the challenge and increase their bargaining power. Then ASEAN is able to moderate the clash of civilization.This essay tries to analye ASEAN’s success in protecting its Moslem members from the clash of civilization, such as interventions and pre-emptive strikes imposed by the US. This is due to the ASEAN’s model of security community which enabled dialogue amongst civilizations possible, especially Confucian and Islamic ones. ASEAN provides the opportunity for its Moslem members to have better bargaining power, such as in the case of Indonesia which has relatively strong power in the ASEAN to direct the courses of the organization. As result the US’s realist approach in the form of security regime had been modified to suit the Indonesian case. Indeed the US should develop dialogue with Moslem in formulating terrorism policies in Indonesia n order to have effective policies that do not endanger human security.